Biophotonics: Photonic Solutions for Better Health Care IV 2014
DOI: 10.1117/12.2051759
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy and SERS analysis of ovarian tumour derived exosomes (TEXs): a preliminary study

Abstract: Here we report a preliminary study based on the application of Raman spectroscopy and surface enhanced Raman spectroscopy (SERS) to investigate the compositional differences between exosomes derived from ovarian carcinoma cells (cell line A2780) grown in normoxia (normal O 2 conditions) and hypoxia (1% O 2 conditions).Exosomes are integral to cell signalling, and are of interest in the study of how cells communicate within their environment. We are particularly interested in identifying whether hypoxia induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Tirinato et al applied SERS on SHS surfaces for the characterization of the spectra from Human colon epithelial (CCD841-CoN) and human colorectal cancer (HCT-116) cell lines [146], whereas Tatischeff et al proved the applicability of RTM to detect changes induced by starvation on Dictyostelium discoideum cells by analyzing their EXOs [161], also reporting the first attempt to characterize EXOs extracted from the urine of human patients. The Raman capacity to reveal modifications in the EXO parental cell conditions was confirmed in 2014 by Kerr et al, which found relevant differences between the spectra of EXOs from ovarian carcinoma cells (A2780) grown in hypoxia and normoxia conditions [156]. This article also reported a useful comparison between gold nanoparticle SERS and Raman microspectroscopy, highlighting the necessity of fine control and optimization of the SERS parameters to avoid thermal damage.…”
Section: Exosome Characterization With Raman Spectroscopy: From Bulk Sample To Single Moleculementioning
confidence: 75%
See 1 more Smart Citation
“…Tirinato et al applied SERS on SHS surfaces for the characterization of the spectra from Human colon epithelial (CCD841-CoN) and human colorectal cancer (HCT-116) cell lines [146], whereas Tatischeff et al proved the applicability of RTM to detect changes induced by starvation on Dictyostelium discoideum cells by analyzing their EXOs [161], also reporting the first attempt to characterize EXOs extracted from the urine of human patients. The Raman capacity to reveal modifications in the EXO parental cell conditions was confirmed in 2014 by Kerr et al, which found relevant differences between the spectra of EXOs from ovarian carcinoma cells (A2780) grown in hypoxia and normoxia conditions [156]. This article also reported a useful comparison between gold nanoparticle SERS and Raman microspectroscopy, highlighting the necessity of fine control and optimization of the SERS parameters to avoid thermal damage.…”
Section: Exosome Characterization With Raman Spectroscopy: From Bulk Sample To Single Moleculementioning
confidence: 75%
“…Henceforth, many other label-free SERS approaches have been exploited for EXO characterization. Most of them relied on the use of gold nanoparticles to create an SERS substrate [142,[153][154][155], or to form a solution composed of EXOs aggregated to Au nanoparticles (GNPs) [156,157]. Other SERS techniques used for EXO characterization are based on different nanostructured arrays, such as high-density Au nanorod (NR) array substrates with Ag nanocubes (NCs) assembled on the NR hot ring [158], nano-bowl arrays covered by a thin Ag film [159], and a hybrid substrate consisting of a graphene-covered Au surface containing a quasiperiodic array of the pyramid [141] (Figure 5e).…”
Section: Exosome Characterization With Raman Spectroscopy: From Bulk Sample To Single Moleculementioning
confidence: 99%
“…When exosomes from healthy and tumorous colon cells were concentrated, the exosomes from tumorous cells showed an identifiably stronger RNA signal in a SERS spectrum, while exosomes from healthy cells showed a stronger lipid spectrum [248]. Exosomes from hypoxic ovarian tumor cells have different biomarkers from normal tumor cells [249]. Exosomes may play a role in cancer signaling, allowing cells to send a command for senescence when treatment starts, and thus increasing the resistance.…”
Section: Detection Of Other Biologically Relevant Nanoparticlesmentioning
confidence: 99%
“…Kerr et al reported SERS analysis on ovarian tumor derived EVs by mixing the EVs with gold nanoparticles 52 , while Tirinato et al showed SERS spectra purportedly arising from EVs on super-hydrophobic nanopillars 53 . However, because the authors did not correct for the SERS signal of the isolation kit used in the study, a substantial portion of that signal is likely to be from that contaminant 48,54 , highlighting some of the difficulty in performing label-free measurements on chemically complex samples such as EVs.…”
Section: B: Surface Enhanced Raman Scattering (Sers)mentioning
confidence: 99%